Managing future oil revenues in Uganda for agricultural development and poverty reduction: A CGE analysis of challenges and options - Manfred Wiebelt; Karl Pauw; John Mary Matovu; Evarist Twimukye; Todd Benson (Kiel Institute for the World Economy (IfW), 2011)
With the recent discovery of crude oil reserves along the Albertine Rift, Uganda is set to establish itself as an oil producer in the coming decade. Total oil reserves are believed to be 2 billion barrels, with recoverable reserves estimated at 0.8-1.2 billion barrels. At peak production, likely to be reached by 2017, oil output will range from 120,000-210,000 barrels per day, with a production period spanning up to 30 years. Depending on the exact production levels, the extraction period, the future oil price, and revenue sharing agreements with oil producers, the Ugandan government is set to earn revenue equal to 10-15 percent of GDP at peak production. The discovery of crude oil therefore has the potential to provide significant stimulus to the Ugandan economy and address its development objectives. However, this is subject to careful management of oil revenues to avoid the potential pitfall of a sudden influx of foreign exchange. Dominating the concerns is the potential appreciation in the real exchange rate and subsequent loss of competitiveness in the non-resource tradable goods sectors such as agriculture or manufacturing ('Dutch Disease'). These sectors are often major employers in developing countries and the engines of growth. Several mitigation measures can be employed by government to counter Dutch Disease, including measures that directly counter the real exchange rate appreciation or measures that offer direct support to traditional export sectors in the form of subsidies. With the aid of a recursive-dynamic computable general equilibrium model this study evaluates the economic implications of the future oil boom in Uganda. We also consider various options open to the Ugandan government for saving, spending, or investing forecasted oil revenues with aim of promoting economic development and reducing poverty, but also countering possible Dutch Disease effects. We find that generally urban sectors and households will be better able to capture rents generated by the oil revenues leading to growing rural-urban and regional inequality. Yet, despite these potential risks, Uganda's oil economy presents an unparalleled opportunity for the agricultural sector and for poverty reduction in particular. On the one hand, domestic demand for food, such as cereals, root crops, pulses and matooke (cooking banana), but especially higher valued products, such as horticulture and livestock products, will increase as incomes rise. Moreover, higher urban income and urban consumer preferences will lead to increasing demand for processed foods and foods with greater domestic value-added, such as meat, fish, etc. Provided Uganda's tradable food sectors can remain competitive, this provides an opportunity for both farming and the food processing manufacturing sector. On the other hand, there is the immediate danger to lose market shares in agricultural export markets, which might be extremely hard to regain after the oil boom. As shown in this paper, the outcomes for agriculture, rural-urban income differentials and poverty reduction depend very much on whether government revenues for public investment in the agricultural sector will increase and help alleviate chronic under-investment in public goods that is constraining agricultural growth in Uganda.
Keywords: 330; Uganda; crude oil; Dutch Disease; agricultural competitiveness; general equilibrium modeling; Mineralölwirtschaft; Staatsfonds; Dutch Disease; Landwirtschaftliche Entwicklung; Internationaler Wettbewerb; Allgemeines Gleichgewicht; Uganda